Cesium Iodide Interface Modification for High Efficiency, High Stability and Low Hysteresis Perovskite Solar Cells. (10th May 2017) - Han, Fei; Luo, Junsheng; Zhao, Bowen; Wan, Zhongquan; Wang, Ruilin; Jia, Chunyang
Graphical abstract: Highlights: CsI as an interface modifier in perovskite solar cell was studied. The CsI interlayer can improve the quality of perovskite film. The CsI interlayer can significantly reduce hysteresis of the device. The CsI-modified device obtains the champion PCE of 17.10%. The optimal device shows good stability over 60 days under atmospheric humidity. Abstract: Each interface is crucial to perovskite solar cells (PSCs), so the interface modification is often used to improve the PV performances. In this manuscript, an environment-friendly cesium iodide (CsI) interface layer between the mesoporous TiO2 (mp-TiO2 ) and the MAPbI3 perovskite active layer was introduced to improve the PV performances and stabilities of PSCs and significantly reduce hysteresis of the device. After optimizing, the PSC employing a CsI-modified mp-TiO2 as electron transporting layer (ETL) could obtain a high fill factor (FF) of 0.79 with an increased power conversion efficiency (PCE) of 17.10% and a low hysteresis index (HI) of 0.10 under illumination of AM 1.5G, while FF of 0.75 and PCE of 14.38% for PSC without CsI interface modification. The enhanced PV performances can be attributed to the improved surface morphology of mp-TiO2, the lower work function (WF) of TiO2, the passivation of surface trap states, the improved perovskite crystallization and reduced grain boundaries. Besides, the reduced WF of TiO2 results in the enhanced built-in potential, which promotes the charge separation, transport and collection.